TRADISI NAUR PANEMPUH DI DESA ADAT SELAT, KECAMATAN SUKASADA, KABUPATEN BULELENG - Suseni Komang Ayu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Bali is rich in traditions, customs and culture. Tradition, custom, culture, and Hindu religion in Bali cannot be separated because Hinduism is the soul of all of them. All of Balinese costums are originated from Hinduism itself. The whole of the customs in Bali, whether related to culture or tradition should be based on the Hinduism. As in the implementation of traditions Naur Panempuh in Selat village , Sukasada district, Buleleng regency full of meaning and teachings of Hinduism itself, traditions Naur Panempuh is a real form of application of hindu religion that is Tri Hita Karana. In this paper will be discussed as follows , (1) How the early history of the implementation of Naur Panempuh Tradition in Selat Village ?, (2) For whom Tradition of Naur Panempuh in Selat Village is applied ?, (3) What the offerings are needed during the procession of Naur Panempuh ?, (4) What is the function or the meaning of Naur Panempuh in Selat Village ?. The contents of each discussion in this paper can be obtained from direct interviewed with holy man or “pemangku” in Selat village who as village secretary also that is Jro Mangku Jasi, the writer interviewed the local people, and also who ever carrid out Naur Panempuh tradition In the traditional village of Selat. The conclusions in this paper are summarized in several subjects: (1) The History of Naur Panempuh Tradition was actually not happened, this tradition existed since the number of adolescent girls married out of the Selat villages and this tradition was the “bhajama” which was obtained by yajna, (2) Tradition Naur Panempuh only applies to people from outside the traditional in Selat village, and applied to all religions, (3) offerings of upakara which must be used at the time of naur panempuh in Pamulungan Agung temple or temple in Selat village are as follows: “Guling “Male Pig” minimum weight + - 60 Kg, or with a minimum money Rp. 2.000.000, - (two million rupiah), Suci Seetan, Pengulap Ambe, Canang Genten, Yellow and White Cloth, and Penang Sari Penebas, (4) the function of Naur Panempuh tradition is seen from the particular purpose is how to limit the volume of adolescent girls from Selat village are married out of the village, and maintain the integrity of Selat village itself and if interpreted widely, then this tradition is the application of Tri Hita Karan in the form of Yadnya.Keywords: Naur Panempuh Tradition, and offerings that is used